"I WISH SOMEONE COULD TELL ME HOW IT FEELS (TO DIE)": COMMUNICATION ABOUT DEATH AND DYING IN ASSISTED LIVING. (11th November 2018) - Vandenberg, A; Bender, A; Kemp, C; Ball, M; Perkins, M
Abstract: Assisted living (AL) is increasingly a site of death, and anxiety about dying has been identified in long-term care residents, their families, and their care staff. Communication about end of life (EOL) in AL has been scripted largely in terms of advanced-care planning and post-death memorialization rather than the dying process itself. To address a gap in knowledge related to desired types of communication, we present a thematic analysis of data from in-depth interviews with 161 participants and 1, 098 site visits at 4 diverse AL communities participating in a 5-year NIA-funded study (End-of-Life in Assisted Living: Links between Structure, Process, and Outcomes, R01AG047408-01A1). Interview participants included: 73 residents (mean age 86, 63% female, 62% white), 51 professional caregivers (71% female, 31% white), and 37 informal caregivers (72% female, 72% white). Residents were at least 85 years of age, had multiple chronic conditions, were diagnosed with a life-limiting illness, and/or used hospice. Participants revealed an array of communication behaviors related to resident death and dying (e.g., information seeking, topic avoidance, deflection through jokes). Tensions emerged when there were differences in levels of desire to talk about death and EOL among residents, informal caregivers, and staff. We present a typology of communication styles and delineate areas of participant concordance and discordance, with implications for reducing death anxiety and improving EOL services and supports in AL.